2013
DOI: 10.1371/journal.pone.0082265
|View full text |Cite
|
Sign up to set email alerts
|

Yet More “Weeds” in the Garden: Fungal Novelties from Nests of Leaf-Cutting Ants

Abstract: BackgroundSymbiotic relationships modulate the evolution of living organisms in all levels of biological organization. A notable example of symbiosis is that of attine ants (Attini; Formicidae: Hymenoptera) and their fungal cultivars (Lepiotaceae and Pterulaceae; Agaricales: Basidiomycota). In recent years, this mutualism has emerged as a model system for studying coevolution, speciation, and multitrophic interactions. Ubiquitous in this ant-fungal symbiosis is the “weedy” fungus Escovopsis (Hypocreales: Ascom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(109 citation statements)
references
References 64 publications
7
92
1
9
Order By: Relevance
“…In culture it produces a brush-like asexual morph with phialides on well-defined vesicles in culture. It differs from Escovopsis by the absence of pigmentation, the lageniform phialides produced on terminal and intercalary, globose vesicles, the hyaline, smooth conidia in long chains, as well as sequence data (Augustin et al 2013). According to the phylogenetic analyses of ITS and LSU sequence data this genus belongs in Hypocreaceae.…”
Section: Fungal Diversitymentioning
confidence: 99%
“…In culture it produces a brush-like asexual morph with phialides on well-defined vesicles in culture. It differs from Escovopsis by the absence of pigmentation, the lageniform phialides produced on terminal and intercalary, globose vesicles, the hyaline, smooth conidia in long chains, as well as sequence data (Augustin et al 2013). According to the phylogenetic analyses of ITS and LSU sequence data this genus belongs in Hypocreaceae.…”
Section: Fungal Diversitymentioning
confidence: 99%
“…However, studies focused on the taxonomy and systematics of filamentous fungi associated with these insects have only considered the genus Escovopsis, the specialized parasite of the mutualistic fungus (Currie et al 1999;Currie et al 2003;Muchovej and Della Lucia 1990;Seifert et al 1995;Augustin et al 2013;Masiulionis et al 2015;Meirelles et al 2015). These studies showed the presence of several new Escovopsis species, which suggests that attine ants colonies might also harbor a high diversity of filamentous fungi, including potential new species of the genus…”
Section: The Authors Also Suggested Cunninghamella Elegans Syncephalmentioning
confidence: 99%
“…This pattern was also repeated with Phomopsis, although some species of the genus are known to produce compounds toxic to insects (Webber 1981), as well as to fungi (Wijeratne et al 2006;Huang et al 2008;Borges et al 2009). An intriguing possibility is that the ants actively prefer material with antifungal properties-if this activity does not affect the basidiomycete mutualist Leucoagaricus but does inhibit ascomycete parasites such as Escovopsis (Augustin et al 2013), then the ants could effectively be medicating their fungal symbiont. Some species of Xylaria are producers of toxins that can have negative effects on both insects (Azevedo et al 2000) and fungi (Boonphong et al 2001), but based on our results, it seems that Xylaria does not represent a threat to the ants or to the fungal symbiont.…”
Section: Fig 2 Continuedmentioning
confidence: 99%